THE DEFINITION OF CARS INDICATORS SAFETY OF BRAKE RETARDERS - Myamlin, S. V.; Kozachenko, D. M.; Harkavi, N. Y. (Science and Transport Progress, 2008)
The basic factors, which affect on safety indices of wagon’s motion on sorting humps, and the interaction between freight wagon wheel and brake retarder are described. The normative indices of wheel stability and the dangerous modes of wagon’s motion on humps are determined.